2021
DOI: 10.1002/hbm.25611
|View full text |Cite
|
Sign up to set email alerts
|

Increased functional interaction within frontoparietal network during working memory task in major depressive disorder

Abstract: Abnormal fronto‐parietal activation has been suggested as a neural underpinning of the working memory (WM) deficits in major depressive disorder (MDD). However, the potential interaction within the frontoparietal network during WM processing in MDD remains unclear. This study aimed to examine the role of abnormal functional interactions within frontoparietal network in the neuropathological mechanisms of WM deficits in MDD. A total of 40 MDD patients and 47 demographic matched healthy controls (HCs) were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…This could explain why M1 primarily identified right hemisphere and central electrodes as important to model performance. It also fits with previous studies that have identified the right hemisphere as particularly overactive in MDD [78], as having increased regional homogeneity [74], as having increased frontal (M2) and fronto-parietal (M3) β-band coherence [79], and as having increased frontoparietal connectivity (M3) related to reduced working memory [80].…”
Section: Resultssupporting
confidence: 89%
“…This could explain why M1 primarily identified right hemisphere and central electrodes as important to model performance. It also fits with previous studies that have identified the right hemisphere as particularly overactive in MDD [78], as having increased regional homogeneity [74], as having increased frontal (M2) and fronto-parietal (M3) β-band coherence [79], and as having increased frontoparietal connectivity (M3) related to reduced working memory [80].…”
Section: Resultssupporting
confidence: 89%
“…Significant depression-by-CM interactive effects on CBF were observed in frontoparietal areas. 30,31 The OFC intimately involves negative thoughts and depressive emotions, regarded as a key target for MDD intervention. 32,33 Previous research reported the effects of OFC on memory conducing to rumination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the DLPFC is involved in emotion regulation in MDD (Nejati et al, 2022), which means that more frequent rumination and a lack of reappraisal are possibly correlated with the DLPFC. Furthermore, Cao et al (2021) suggested that MDD patients had abnormal connectivity between the right inferior parietal lobule and the right DLPFC. Therefore, overactivity in the PFC of MDD patients occurs in order to compensate for a lack of deactivation in regions of the default mode network (DMN) (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%